2012
DOI: 10.1111/pde.12035
|View full text |Cite
|
Sign up to set email alerts
|

Linear Congenital Molluscum Contagiosum on the Coccygeal Region

Abstract: Congenital molluscum contagiosum is rare but has been reported previously. We present a unique case of linear congenital molluscum on the coccygeal region. To make a correct diagnosis, avoid unnecessary examination, and start appropriate treatment as soon as possible, it is beneficial for dermatologists to be aware that molluscum contagiosum can present at birth and can be linear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…An epidemiological study revealed that the most commonly affected sites were the lower limbs, and the importance of skin-to-skin contact for the contracting the virus has also been suggested (1,2). Infantile cases are relatively rare because of presumed transmitted immunity from maternal antibodies (2), but some cases have been sporadically reported as birth canal infection (3-5) and documented as congenital (3,4). However, the nodule in the current patient was noticed one month after birth, thus it is possible that the virus was contracted thorough other modes of transmission, such as contaminated fomites or latent infection on the guardians' hands, which can be a cause of direct transmission during procedures, such as changing nappies, although palms and soles are as rarely affected as mucous membranes (6,7).…”
Section: Diagnosis: Molluscum Contagiosummentioning
confidence: 99%
“…An epidemiological study revealed that the most commonly affected sites were the lower limbs, and the importance of skin-to-skin contact for the contracting the virus has also been suggested (1,2). Infantile cases are relatively rare because of presumed transmitted immunity from maternal antibodies (2), but some cases have been sporadically reported as birth canal infection (3-5) and documented as congenital (3,4). However, the nodule in the current patient was noticed one month after birth, thus it is possible that the virus was contracted thorough other modes of transmission, such as contaminated fomites or latent infection on the guardians' hands, which can be a cause of direct transmission during procedures, such as changing nappies, although palms and soles are as rarely affected as mucous membranes (6,7).…”
Section: Diagnosis: Molluscum Contagiosummentioning
confidence: 99%
“…One 2012 case report identified a linear track of molluscum lesions in the coccygeal region with additional lesions presenting on the back and upper arm in a 1-year-old infant. 28 It is possible to confirm the mode of transmission through viral genotyping, but to date, no studies have examined the genotype of congenital molluscum lesions. As in the case of sexually transmitted molluscum, the main therapy for congenital molluscum lesions is direct destructive measures with curettage or cryotherapy.…”
Section: Molluscum In Pediatric Patientsmentioning
confidence: 99%
“…However, Molluscum contagiosum can have an atypical presentation, more frequently when there is an immunodepression condition such as: AIDS (acquierd immunodeficiency syndrome), Viskott Aldrich Disease, malignant lymphoma [3], and it can appear larger (more than 1 cm), eczematous or abscessed and sometimes refractory to the usual treatment [4]. In the literature, the linear presentation has been reported in one case of a new born who Letter to the Editor had a a unique linear plaque composed of many small molluscum papules on the coccygeal region present since birth [5]. In our patient, the linear distribution was confusing us and other diagnosis was evocated such are linear epidermal nevus and contact dermatitis.…”
mentioning
confidence: 99%